Initial results with (18F)FAPI‑74 PET/CT in idiopathic pulmonary fibrosis - Mori, Yuriko; Kramer, Vasko; Novruzov, Emil; Mamlins, Eduards; Röhrich, Manuel; Fernandez, Rene; Amaral, Horacio; Soza-Ried, Cristian A.; Monje, Barbara; Sabbagh, Eduardo; Florenzano, Matias; Giesel, Frederik L.; et al. (European journal of nuclear medicine and molecular imaging, 2023)
Idiopathic pulmonary fibrosis (IPF) is a chronic fibrosing interstitial lung disease with a poor prognosis. Ga-68-labeled FAP ligands exhibited highly promising results due to the crucial role of activated fibroblasts in fibrosis imaging of the lung. However, F-18-labeled FAP ligands might provide qualitatively much higher imaging results with accompanying economic benefits due to large-scale production. Thus, we sought to investigate the potential of [F-18]FAPI-74 prospectively in a small patient cohort.Methods: Eight patients underwent both [F-18]FAPI-74-PET/CT and HRCT scans and were then compared with a control group without any fibrosing pulmonary disease. The tracer uptake of fibrotic lung areas was analyzed in synopsis with radiological and clinical parameters.Results: We observed a positive correlation between the fibrotic active volume, the Hounsfield scale, as well as the vital and diffusing capacity of the lung.Conclusion: The initial results confirm our assumption that [F-18]FAPI-74 offers a viable non-invasive assessment method for pulmonary fibrotic changes in patients with IPF.
Im Titel steht 18F in eckiger Klammer, die Zahl 18 ist dabei hochgestellt
Gesehen am 11.03.2024